Comparative Study of Buffalo and Cow Milk Feta‐Type Cheese with Respect to Sensory and Biochemical Characteristics during Ripening. Issue 3 (24th October 2012) - Kumar, Sanjeev; Kanawjia, S.K.; Kumar, Suryamani; Khatkar, Sunil
Abstract The effect of type of milk on sensory and biochemical characteristics of feta‐type cheeses was investigated during the ripening period. Both types of milk were standardized to casein/fat ratio of 0.70. The overall flavor, body and texture score for cow milk feta‐type cheese was found significantly (P < 0.05) higher than the buffalo milk feta‐type cheese, but the overall color and appearance score was found significantly (P < 0.05) higher in buffalo milk feta‐type cheese. The pH of buffalo milk feta cheese was found significantly (P < 0.05) higher than the cow milk feta‐type cheese. In addition to that, the percentage titratable acidity, soluble protein and free fatty acid value were found significantly (P < 0.05) higher in cow milk feta cheese throughout the ripening period. Practical Applications Traditionally, feta cheese is made from ewe's milk or its mixture with goat's milk. The production of ewe and goat milk is around 2% of the world's total milk production. That is why it becomes almost impossible to fulfill the demand of feta cheese particularly from such milk. However, cow milk is readily available throughout the world. So, in order to fulfill the ever‐growing demand of feta cheese worldwide, the technology for manufacture of acceptable quality cheese from cow milk has been successfully developed. The preferred characteristic of feta cheese is white in color; generally, cow milk is bleached in order to obtain white color. But bleaching destroys valuable β‐carotene, which is a major disadvantage of cow milk cheese. However, in India 57% of total milk production comes from buffalo. Therefore, there is a need to develop adaptable technology for manufacture of feta cheese from buffalo milk.